2021
DOI: 10.1021/acs.analchem.1c01336
|View full text |Cite
|
Sign up to set email alerts
|

Faradaic Counter for Liposomes Loaded with Potassium, Sodium Ions, or Protonated Dopamine

Abstract: Collisional electrochemistry between single particles and a biomimetic polarized micro-liquid/liquid interface has emerged as a novel and powerful analytical method for measurements of single particles. Using this platform, rapid detection of liposomes at the single particle level is reported herein. Individual potassium, sodium, or protonated dopamine-encapsulated (pristine or protein-decorated) liposomes collide and fuse with the polarized micro-liquid/ liquid interface accompanying the release of ions, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Although the blocking method is an efficient single collision technique for determining the frequency and the height of the current steps during the particle adsorption onto the UME surface [4,14,42,44,45], the reactor method brings more information on the mechanism of the electroporation process and the liposome content release [4,9,15,33,46]. The liposomes size distribution calculated from the charge passed in each current spike (by peak integration) in the i-t curve is a crucial information on the electrolysis process occurring upon impact onto the UME surface.…”
Section: Electrochemical Single Impacts Of Synthetic Redox Liposomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the blocking method is an efficient single collision technique for determining the frequency and the height of the current steps during the particle adsorption onto the UME surface [4,14,42,44,45], the reactor method brings more information on the mechanism of the electroporation process and the liposome content release [4,9,15,33,46]. The liposomes size distribution calculated from the charge passed in each current spike (by peak integration) in the i-t curve is a crucial information on the electrolysis process occurring upon impact onto the UME surface.…”
Section: Electrochemical Single Impacts Of Synthetic Redox Liposomesmentioning
confidence: 99%
“…The liposomes size distribution calculated from the charge passed in each current spike (by peak integration) in the i-t curve is a crucial information on the electrolysis process occurring upon impact onto the UME surface. In this way, several recent investigations deal with the permeability of the liposomes lipid membrane and the effect of the membrane tension on the liposomes content release based on single impact events [9,15,44,46]. Especially, Zhang et al [9] have found that the liposomes electroporation process and the amount of released ferrocyanide content can be controlled by modifying the osmolarity of the buffer in which the 200 nm diameterliposomes are suspended.…”
Section: Electrochemical Single Impacts Of Synthetic Redox Liposomesmentioning
confidence: 99%
See 2 more Smart Citations
“…When a single nanoparticle collides with the microelectrode surface by random Brownian motion, it can generate a transient current by hindering electron transfer and self-reaction or catalyzing electroactive substances. Each effective collision can produce an independent and distinguishable step or peak current. By measuring the current intensity, frequency, current rise time, or life, the size distribution, agglomeration degree, , concentration, electrocatalytic properties, and other properties of NPs in the solution can be directly analyzed in situ . Lemay et al first proposed blocking SPCE to realize electrochemical characterization and measurement of individual insulating particles, which has been regarded as one of the most attractive nanometer-scale analytical methods .…”
mentioning
confidence: 99%